Jacques Viger: une biographie. Suivi des lettres de Jacques et Marguerite, 1808-1813 - Beaudoin, Léo; Blanchet, Renée (Études québécoises, 2009)
Keywords: Lacorne (famille); Maires; Milice; Société historique de Montréal; Viger, Jacques

The Riot that Never Was: The Military Shooting of Three Montrealers in 1832 and the Official Cover-Up - Jackson, James (Baraka Books, 2009)
Keywords: Armée; Irlandais; Tracey, Daniel; Émeutes

Le fort et les poudrières du complexe militaire de l'île Sainte-Hélène - Royer, Martin (Université Laval, 2009)
Keywords: Armes; Fortifications; Forts; Île Sainte-Hélène

Le Québec à l'heure de la Révolution américaine - Boyer, Jean-Pierre (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Du Calvet, Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Journalistes; Librairie; Mesplet, Fleury

Le Roi, l'Église et la guerre: la prédication à Montréal au moment de la conquête (1750-1766) - Décary, Simon (Université de Montréal, 2008)
Keywords: Communautés religieuses; Sulpiciens

Les Pointeliers en guerre - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2008)
Keywords: Armée; Guerre; Milice; Pointe-aux-Trembles; Quartiers

La stratégie lors de l'affrontement anglo-américain au Canada (1775-1776). Objets politiques et objectifs militaires - Nadeau, Charles André (Université Laval, 2008)
Keywords: Américains; Armée; Britanniques

Iberville et les historiens. Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Histoire; Historiens; Le Moyne d'Iberville et d'Ardillières, Pierre

Fighting from Home. The Second World War in Verdun, Quebec - Durflinger, Serge Marc (Studies in Canadian Military History Series, 2006)
Keywords: Guerre; Quartiers; Verdun

A Man's a Man because of That: The Scots in the Canadian Military Experience - Klepak, H. P. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Armée; Écossais

WILSON, ERASTUS WILLIAM - Gagnon, Jean-Pierre (Dictionnaire biographique du Canada, 2005)

RODDICK, sir THOMAS GEORGE - Hanaway, Joseph (Dictionnaire biographique du Canada, 2005)

La milice du district de Montréal, 1787-1829: essai d'histoire socio-militaire - Lépine, Luc (Université du Québec à Montréal, 2005)
Keywords: Milice

MEREDITH, sir HENRY VINCENT - McDowall, Duncan (Dictionnaire biographique du Canada, 2005)

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

VALLÉE, CHARLES-AMÉDÉE - Tremblay, Marie J. (Dictionnaire biographique du Canada, 2005)

James McGill of Montreal : citizen of the Atlantic world - Cooper, John Irwin (Borealis Press, 2003)
Keywords: Autochtones; Fourrure; Marchands; McGill, James

The Last French and Indian War: an Inquiry Into a Safe-Conduct Issued in 1760 that Acquired the Value of a Treaty in 1990 - Vaugeois, Denis (McGill-Queen's University Press et Septentrion, 2002)
Keywords: Autochtones; Français

L'organisation de la milice de la région montréalaise de 1792 à 1837: de la paroisse au comté - Dion, Dominique; Legault, Roch (Bulletin d'histoire politique, 2000)
Keywords: Milice